Plan de marketing del Restaurante Atatay Que Rico - Parodi Gallo, Paola Patricia (2012)
“Atatay Que Rico” located in front of Universidad Indoamericas new campus, north of Quito, offers its clients fast food and an a la carte menu This Marketing plan seeks greater market share, generating as a result an increase in sales In the situational analysis it was observed that the factors affecting both, the macro environment and the microenvironment are mostly favorable, which indicates that it is viable to develop the marketing strategies needed to increase profitability in the short term; and the reduction of production costs by taking advantage of the strengths and opportunities recognized. Through market research, It was achieved valuable information about the degree of satisfaction of current customers, where it was determined that it is necessary to continuously improve key areas, such as, customer service, quality, taste, price and variety for the company to achieve the levels of excellence intended; referring to potential clients, market research revealed that the market segment that the company should direct its efforts to capture greater market share, are those between 20 and 30 years old, who search as a restaurant most important attributes, cleanliness and taste of the food…